Polymorphism p.402Y>H in the complement factor H protein is a risk factor for age related macular degeneration in an Italian population. Issue 9 (14th June 2006) - Simonelli, F; Frisso, G; Testa, F; di Fiore, R; Vitale, D F; Manitto, M P; Brancato, R; Rinaldi, E; Sacchetti, L
Abstract : Aims: To evaluate the complement factor H (CFH) p.402Y>H polymorphism as a risk factor in age related macular degeneration (AMD) in an Italian population. Methods: 104 unrelated Italian AMD patients and 131 unrelated controls were screened for the CFH polymorphism p.402Y>H (c.1277 T>C), which has been associated with AMD. Retinography was obtained for patients and controls; the AMD diagnosis was confirmed by fluorescein angiograms. The c.1277 T>C polymorphism was genotyped with the TaqMan real time polymerase chain reaction single nucleotide polymorphism assay. Results: The frequency of c.1277C allele was higher in AMD patients than in controls (57.2% v 39.3%; p<0.001). The odds ratio (OR; logistic regression analysis) for AMD was 3.9 (95% confidence interval (CI): 1.9 to 8.2) for CC homozygotes. The CC genotype conferred a higher risk for sporadic (OR 4.6; CI: 2.0 to 10.5) than for familial AMD (OR 2.9; CI: 1.0 to 8.4). Genotypes were not related to either age at AMD diagnosis or to AMD phenotype. However, geographic atrophy and choroidal neovascularisation were more frequent in sporadic than in familial AMD (p = 0.027). Overall, the percentage of population attributable risk for the CC genotype was 28% (95% CI:18% to 33%). Conclusion: The association between the p.402Y>H (c.1277T>C) polymorphism and AMD applies to the Italian population and the CC genotype is more frequent in sporadic than in familial AMD cases.